1981
DOI: 10.2337/diab.30.9.792
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Transformation of Glucagon-Like Immunoreactivity of Gut into Pancreatic Glucagon In Vivo

Abstract: SUMMARYThe effect of gut glucagon-like immunoreactivity (GLI) devoid of pancreatic glucagon was studied in piglets. All glucagon-like peptides with an accessible C-terminal were removed from the gut extract by specific antibodies reacting with the C-terminal of the glucagon molecule. Endogenous secretion of pancreatic and gut glucagon was blocked by somatostatin infusion, and then the purified gut glucagon preparation was infused. The latter prevented the hypoglycemia resulting from somatostatin infusion, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Possibly, the two components identified in plasma from pancreatectomized patients are identical to the forms found in human tissue extracts. However, the presence in plasma of these components with C-terminal immunoreactivity might also be due to hydrolysis within the circulation of the components with C-terminal extensions as suggested by Korany et al [20]. This mechanism might also explain the initial increase in the concentration of C-terminal immunoreactivity, which coincided with the peak of the 6-15 immunoreactivity response to the test meal.…”
Section: Discussionmentioning
confidence: 81%
“…Possibly, the two components identified in plasma from pancreatectomized patients are identical to the forms found in human tissue extracts. However, the presence in plasma of these components with C-terminal immunoreactivity might also be due to hydrolysis within the circulation of the components with C-terminal extensions as suggested by Korany et al [20]. This mechanism might also explain the initial increase in the concentration of C-terminal immunoreactivity, which coincided with the peak of the 6-15 immunoreactivity response to the test meal.…”
Section: Discussionmentioning
confidence: 81%
“…A similar and corro borating result has been obtained by Besterman et al [21] who found an excessive postcibal release of enteroglucagon in coeliac dis ease in which the ileum is hypertrophied and exposed to a large amount of unabsorbed food. The enteroglucagon molecule contains the entire sequence of 'pancreatic' glucagon [22,23] and may be a precursor of glucagon in the islet cells [24], Furthermore, there is some evidence that the circulating enteroglu cagon may act as such precursor [25]. It is still unknown what the function of circulating enteroglucagon is.…”
Section: Discussionmentioning
confidence: 99%
“…The continuing increase after the meal in the bypass patients may reflect a cor responding secretion, the reason for which could be deinhibition because of the low glu cose levels, but another possibility is that a small fraction of the large amount of circula tion enteroglucagon has been broken down to fragments reacting in the assay [25], PP is secreted from pancreas under con trol of the vagal, cholinergic system [5], It was not expected that the bypass operation influences the PP secretion, and this was con firmed by our results as well as by those of Sarson et al [1], They found a severe reduc tion of the PP response after biliopancreatic bypass, which involves a partial gastrectomy and a long Roux-en-Y gastroenterostomy. The reduction is probably due to damage of vagal fibres to the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in man [26] suggest that neither of these possibilities makes a significant contribution to plasma enteroglucagon estimates. Although Koranyi et al [27] have shown conversion of glucagon-like immunoreactivity to immunoreac tive glucagon in the circulation, our chro matographic studies provide no evidence of a major degree of such interconversion in the rat, as only the Kav 0.25 molecular form of glucagon-like immunoreactivity is signifi cantly elevated. Smaller forms of glucagon like immunoreactivity in the Kav 0.58 peak seem only to have undergone a minor non significant degree of elevation in the resected rats.…”
Section: Discussionmentioning
confidence: 37%